2022
DOI: 10.1002/clc.23888
|View full text |Cite
|
Sign up to set email alerts
|

QT and Tpeak‐Tend interval variability: Predictive electrical markers of hospital stay length and mortality in acute decompensated heart failure. Preliminary data

Abstract: Background As previously reported, an increased repolarization temporal imbalance induces a higher risk of total/cardiovascular mortality. Hypothesis The aim of this study was to assess if the electrocardiographic short period markers of repolarization temporal dispersion could be predictive of the hospital stay length and mortality in patients with acutely decompensated chronic heart failure (CHF). Method Mean, standard deviation (SD), and normalized variance (VN) of QT (QT) and Tpeak‐Tend (Te) were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It was also found that in patients with heart failure with a reduced ejection fraction (HFrEF), mean Tp-e and its standard deviation were higher than in those with heart failure with preserved ejection fraction (HFpEF) [ 82 ]. However, Son et al found no difference in Tp-e and Tp-e/QT ratio based on ejection fraction in three groups of heart failure patients (preserved, midrange, and reduced ejection fraction) [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was also found that in patients with heart failure with a reduced ejection fraction (HFrEF), mean Tp-e and its standard deviation were higher than in those with heart failure with preserved ejection fraction (HFpEF) [ 82 ]. However, Son et al found no difference in Tp-e and Tp-e/QT ratio based on ejection fraction in three groups of heart failure patients (preserved, midrange, and reduced ejection fraction) [ 86 ].…”
Section: Resultsmentioning
confidence: 99%